A Iminência do Samba: análise do processo de criação da coreografia O Samba do Criolo Doido - Barbosa, Luiz Augusto (Luiz de Abreu) (2016)
This research offers a presentation and analysis of Luiz de Abreu‟s dance performance O Samba do Criolo Doido (“The Samba of the Crazy Nigger”), examining the choreographer‟s creative process as well as the creative contexts and the work‟s evolutions and offshoots. The writing process is based upon the method of “bricolage,” using as a point of departure cartographic and autoethnographic procedures in which the artist‟s body is viewed as a field, in relation to other fields, i.e. the observer who observes himself in a transversal sense in which there is no separation between subject and object, practice and theory, knowledge and politics. Further procedures adopted involve the disassembly and rewriting of the “text” with the aim of sharing an active reflection on the creative process in terms of ethics and aesthetics. In addition to the scenic elements, the black body is analyzed as a field of study, as well as a device of profanation, a political territory, and a body in transformation. Impregnated with historical and cultural importance and symbolism, such elements contribute to the construction of the image of black men and women in Brazil.